The Evaluation of Agronomic Traits of Wild Soybean Accessions (Glycine soja Sieb. and Zucc.) in Heilongjiang Province, China - Wei Li; Mu Peng; Zhen Wang; Yingdong Bi; Miao Liu; Ling Wang; Shufeng Di; Jianxin Liu; Chao Fan; Guang Yang; Deyue Yu (Agronomy, 2021)
Wild soybean germplasm is distributed widely in China, particularly in Heilongjiang Province. In this study, 242 wild soybean accessions from four agricultural divisions in Heilongjiang Province were evaluated based on six qualitative and eight quantitative traits. Results showed that a large amount of variation occurred in these evaluated traits. Abundant qualitative traits included the wild type (78.51%), purple flowers (90.50%), needle leaf (39.26%), black seed (83.88%), brown hilum (52.07%), and mud film (87.60). Results of multivariate analysis based on quantitative traits showed that 100-seed weight, seeds weight per plant, number of seeds per plant, number of effective pods, and number of invalid pods were significantly different among samples (p < 0.05). A total of 27 germplasms were screened. Cluster analysis identified the 242 accessions into two groups, not following the geographical distribution pattern, with rich wild soybean resources revealed in the northern site. The present study indicated that wild soybean in Heilongjiang Province should be conserved in situ. The rich genetic diversity revealed in soybeans of different sites in Heilongjiang Province suggested its significant potential utilization in genetic improvement and breakthrough for soybean breeding. This information will help to exploit and conserve wild soybean accessions in Heilongjiang Province.